Experiences of kinship foster parents - Swanepoel, Judith Magrietha (Rhodes University, Faculty of Humanities, Department of Social Work)
Kinship foster care as a field of study in social work has been neglected in South Africa. The difficulties currently experienced in obtaining unrelated foster parents, warrant a closer look at kinship foster care. The aim of this study was to gain an understanding of the distressing and joyful experiences of kinship foster parents in fostering a relative's child. Their role as kinship foster parents, and how it relates to their role as a relative of the child, was explored. The study further explored the impact which kinship foster care may have on the kinship parents' relationship with their extended family. A literature study was undertaken during which it was evident that kinship foster care is becoming increasingly popular as a placement option for children needing out-of-home care. An interview schedule was constructed and administered to the entire population, of one welfare organisatiOI:t, consisting of seventeen kinship foster parents. Twelve kinship foster parents participated in the study. This study therefore provides a limited picture on kinship foster care. The overall findings in this study showed that the majority of children in kinship care are cared for by the maternal families. When the respondents experience problems in obtaining the foster care grant, it could influence their relationship with the social workers. It seemed as if foster parents are under the impression that it is the task of social workers to see to the payments of these grants. From the sample, it seemed as if kinship foster parents are mostly sympathetic towards problems experienced by social workers which hinder them in their service delivery, and are willing to contact them if they experience any problems. It seemed as if most kinship foster parents enjoy fostering the child and receive emotional and financial support from their friends and family. Kinship foster parents' elationships with their family members (the parent of the child) could be influenced by that family member's involvement with a partner. The respondents were of the opinion that the relationship tends to be better if they accepted the partner of the parent as suitable
Keywords: Kinship care -- South Africa; Foster children -- South Africa; Foster parents -- South Africa